Scrutinizing the sport pyramid metaphor: an examination of the relationship between elite success and mass participation in Flanders - de Bosscher, V.; Sotiriadou, P.; van Bottenburg, M. (International Journal of Sport Policy and Politics, 2013)
Many governments use the trickle-down or demonstration effect to justify their high investments in an elite sport. The assumption is that elite success increases mass participation. Evidence of a relationship between elite success and mass participation is fragmented, and previous studies have mostly failed to demonstrate a connection. Nevertheless, many authors assert the need for more research on this relationship. This study examines the effect of elite sport on mass participation. The study uses Pearson's correlations to analyse the relationship between membership data and athlete success (using the elite sport index) in Flanders over the past 15 years. The membership figures from Flanders were compared with figures from the Netherlands to identify the common trends. Analysis across 20 sports revealed no consistent relationship between membership levels and success. Positive correlations were notable in Flanders in four of the eight sports in which elite Flemish competitors achieved significant international successes during the study period (athletics, gymnastics, judo and tennis). The analysis suggests that a trickle-down effect is not likely to occur automatically but might be found under specific conditions. This leads us to call for new studies that bypass the question of whether there is such a relationship and concentrate on why, how and when this relationship occurs.